Erratum to: Lubrication of dry sliding metallic contacts by chemically prepared functionalized graphitic nanoparticles - Suprakash Samanta; Santosh Kumar Singh; Rashmi R. Sahoo (Friction)
The original version of this article unfortunately contained incorrect author’s name and address. On the first page of this article, instead of Suprakash SAMANTA 1,2, Santosh SINGH 1, Rashmi R. SAHOO 1,2,* 1 Surface Engineering & Tribology Division, CSIR-Central Mechanical Engineering Research Institute, Durgapur 713209, India 2 Academy of Scientific and Innovative Research (AcSIR), Ghaziabad 201002, India It should read Suprakash SAMANTA 1,2, Santosh Kumar SINGH 1, Rashmi R. SAHOO 1,2,* 1 Enviromental Engineering Group, CSIR-Central Mechanical Engineering Research Institute, Durgapur 713209, India 2 Academy of Scientific and Innovative Research (AcSIR), Ghaziabad 201002, India